PCS-6 Preparation and Application of Nano Chitosan Particles as Adjuvan in Rabies Vaccination Based on Anti-Idiotype Antibody - Sayu Putu Yuni Paryati; K Hasan; S Ramadhanti (Hemera Zoa, 2018)
Rabies is a fatal disease to humans and animals, but can be controlled by prophylaxis administration before being exposed. One type of vaccine that can be utilized is an anti-idiotype antibody vaccine originating from IgY purification of chicken egg yolk. The use of vaccine additives in the form of adjuvants is very important to improve the effectiveness of vaccines [1].Chitosan is non-toxic, easily synthesized, safe to use and able to induce an immune response by activating macrophages. Chitosan can modulate dendritic cell maturation so that it can induce interferon interactions and stimulate activity of T lymphocytes and B lymphocytes. Chitosan can be made in the form of chitosan nanoparticles that can be used to deliver drugs and vaccines through inhalation pathways, orally, intravenously and as non-viral gene delivery vectors. In the oral delivery of chitosan nanoparticles are able to overcome the problem of solubility, protect the drug from enzymatic degradation, controlled release, and extend the time of action in the bloodstream through ionic mechanisms with mucin. Inhalation of chitosan 0.5mg/ml with influenza vaccine produces a good response [2-4].In this work, the preparation of chitosan nanostructures and their application as adjuvan in antibody anti-idiotype rabies vaccination were reviewed.